Dakwah Moderat Abdurrahman Wahid di Kalangan Kelompok Minoritas - Imam Hakim (STAIN Bengkalis, 2020)
This research discusses Abdurrahman wahid’s moderate da’wah among minority groups. This departs from their proximity to minority groups so that their presence can be accepted by then both on behalf of ethnicity, culture and religion. His preaching among minorities is indeed a problem in itself. Various accusations against him are often heard, especially from right-wing Islamic groups such as the FPI. Even openly, the great leader of the FPI Habib Rizeq considered Abdurrahman wahid to be blind and blind in heart. In addition to that among NU itself, Gus Dur was also considered a controversial cleric because he protected minority people and was too strict with his own Islamic groups. This attitude was later considered as a figure who embraced liberal Islam. This research is a research library research using qualitative descriptive analysis. The results showed that the method of da’wah used by Abdurrahman wahid departed from his understanding of al-Qur’an, Hadist and the foundation of the ulama Ahlusunnah Wal-Jama’ah, namely conveying teachings thraougg love. Da’wah as a method of inviting must reflect the values of Islamic teachings that are humanist, full of compassion for fellow humans as part of the essences of god’s teachings that are Ar-Rahman and Ar-Rahim. In this way, Islamic teachings could be accepted throughout the archipelago.